SAE Technical Paper Series 2010
DOI: 10.4271/2010-01-1931
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Hybridization of a Class 8 Line-Haul Truck

Abstract: Hybrid electric vehicles have demonstrated their ability to significantly reduce fuel consumption for several medium-and heavy-duty applications. In this paper we analyze the impact on fuel economy of the hybridization of a tractor-trailer. The study is done in PSAT (Powertrain System Analysis Toolkit), which is a modeling and simulation toolkit for light-and heavy-duty vehicles developed by Argonne National Laboratory. Two hybrid configurations are taken into account, each one of them associated with a level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…Three approaches can be used to improve the fuel economy and/or reduce GHG emissions of heavy-duty trucks: non-electrification efficiency-improving technologies on conventional powertrains and vehicles [1][2][3], hybrid powertrain technologies [3][4], and the substitution of natural gas, electricity or hydrogen for diesel fuel [5][6]. All of these approaches have the potential to reduce GHG emissions from the transportation sector.…”
Section: Introductionmentioning
confidence: 99%
“…Three approaches can be used to improve the fuel economy and/or reduce GHG emissions of heavy-duty trucks: non-electrification efficiency-improving technologies on conventional powertrains and vehicles [1][2][3], hybrid powertrain technologies [3][4], and the substitution of natural gas, electricity or hydrogen for diesel fuel [5][6]. All of these approaches have the potential to reduce GHG emissions from the transportation sector.…”
Section: Introductionmentioning
confidence: 99%
“…There are on-going projects on the design of the hybrid drivetrain for the class-8 trucks [7][8]. One fifth of the total US truck fuels is consumed by line-haul trucks [7], which shows the worthwhile potential to develop hybrid electric drivetrain for these vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The primary motivation behind this was to compare the fuel economy improvements that can be achieved by the hybridization of a diesel-based powertrain and a gas-based powertrain. It is assumed that such a powertrain modification could be relevant for those HD vehicles, whose operating schedules include a considerable share of city and suburban haulage since the major effect of HD powertrain hybridization is expected in conditions allowing for intensive use of regenerative braking, which is the most efficient tool for increasing the fuel economy of vehicles with large masses [10].The published studies (see, for example, [11][12][13][14]) have demonstrated that hybrid HD vehicles having a gross mass ranging 16 to 36 tons possess a significant fuel-saving potential in city driving conditions, especially in the case of full hybridization, which offers up to 35% fuel consumption reduction. The mild degree of hybridization is able to provide moderate fuel savings of about 10%.…”
Section: Introductionmentioning
confidence: 99%